STUDYING THE INCIDENCE OF ALLERGIC DISEASES AMONG CHILDREN LIVING IN DIFFERENT REGIONS - Achilova D.N. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. Science and medicine have not yet made accurate conclusions about why allergies can develop in children. However, there are certain factors that contribute to the development of allergic reactions in a baby. Allergy is not a disease in the usual sense of the word. Allergy is a very strong reaction of the child's immune system, which occurs exclusively with repeated contact with an irritant (allergen). This is the complexity of the diagnosis of pathology. At the first contact with an allergen, the immune response does not always manifest itself.